1994
DOI: 10.1007/bf00325888
|View full text |Cite
|
Sign up to set email alerts
|

Spruce budworm growth, development and food utilization on young and old balsam fir trees

Abstract: Laboratory rearing of spruce budworm, Choristoneura fumiferana, in conjunction with field rearing, gravimetric analyses, a transfer experiment, and foliage chemical analyses at six dates during the period of budworm feeding activity indicated that the age of balsam fir, Abies balsamea, trees (70-year-old mature trees or 30-year-old juvenile trees) affected tree suitability for the spruce budworm via the chemical profile of the foliage. Insects reared on old trees had greater survival and pupal weight, shorter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 30 publications
1
106
0
5
Order By: Relevance
“…The dry weight of frass produced in each rearing sleeve cage was recorded, pupae were weighed, and moth emergence was monitored every half hour, 24 h a day. Results from a study on spruce budworm food utilization that combined laboratory and field rearing experiments indicated that the rearing technique used in the present study gives an accurate estimate of h s s production (Bauce et al 1994). On each 55-cm-long branch, the total amount of c m t -y e a r foliage produced (AFP), the amount of current-year foliage destroyed by the larvae (AFD) and the amount of residual current-year foliage remaining on each branch after budworm defoliation (ARF) were determined using Bauce et al (1994) methodology by (1) determining, for each tree, using two north-northwest facing midcrown uninfested branches, the number of needles per cm of current-year twigs, and the mean dry weight of a needle, (2) measuring on the budworm infested branches the total length of current-year twigs, (3) measuring the length of defoliated twigs, (4) converting cm of twigs in number of needles, and (5) converting number of needles in weight of foliage.…”
Section: Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…The dry weight of frass produced in each rearing sleeve cage was recorded, pupae were weighed, and moth emergence was monitored every half hour, 24 h a day. Results from a study on spruce budworm food utilization that combined laboratory and field rearing experiments indicated that the rearing technique used in the present study gives an accurate estimate of h s s production (Bauce et al 1994). On each 55-cm-long branch, the total amount of c m t -y e a r foliage produced (AFP), the amount of current-year foliage destroyed by the larvae (AFD) and the amount of residual current-year foliage remaining on each branch after budworm defoliation (ARF) were determined using Bauce et al (1994) methodology by (1) determining, for each tree, using two north-northwest facing midcrown uninfested branches, the number of needles per cm of current-year twigs, and the mean dry weight of a needle, (2) measuring on the budworm infested branches the total length of current-year twigs, (3) measuring the length of defoliated twigs, (4) converting cm of twigs in number of needles, and (5) converting number of needles in weight of foliage.…”
Section: Methodsmentioning
confidence: 72%
“…An additional 100 mg of dried foliage was extracted three times with 70% acetone containing 0.1% ascorbic acid (Dement and Mooney 1974;Wisdom et al 1987) and the resulting liquid phase was analyzed for total tannins using the technique of radial diffision in agar medium with BSA protein (Hagerman 1987), and for total phenolics using the Folin-Denis reaction (Swain and Hillis 1959). Two additional subsamples of fresh twigs were collected, placed in crimped seal vials and kept at-20°C until needles were analyzed for monoterpene contents using the methodology descri'oed in Bauce et al (1994). The experiment was repeated using different trees in 1993.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Donc l'ensoleillement aurait une influence sur l'invasion d'une branche par la TBE. Mais une trop forte concentration de monoterpènes agiraient négativement sur la croissance des larves du 6 ème stade (Bauce et al, 1994). Aucune littérature n'a encore traité en détail, l'effet des monoterpènes sur la croissance des larves des premiers stades.…”
Section: Effets De L'éclaircie Commercialeunclassified
“…Malgré que les mécanismes n'en soient pas vraiment élucidés, la survie des semis de sapin sous le couvert forestier est meilleure que celle des sapins dominants (MacLean et Piene, 1994;Reams, 1988;Miller, 1977). Bauce et al (1994) ont trouvé que des variations de la qualité du feuillage des sapins reliées à l'âge de ceux-ci, peuvent expliquer la performance accrue des larves de la tordeuse se nourrissant sur les sapins de 70 ans comparativement aux sapins de 30 ans.…”
Section: Mise En Garde/adviceunclassified